Human Cytomegalovirus Up-regulates Nuclear Factor-κB in Women with Spontaneous Abortion - Asmaa’ Baqer Al-Obaidi (مجلة كلية الطب, 2009)
Background: Human cytomegalovirus (HCMV) infection during pregnancy causing serious problems through induction of viral genes that enhance the expression of different cellular factors ending in failure of pregnancy. Patients and Methods: Paraffin embedded sections of curate samples were obtained from 34 women had spontaneous abortion, and 5 women had elective termination of pregnancy (as control), and then subjected for immunohistochemistry analysis to detect human cytomegalovirus (HCMV) early protein, and in situ hybridization technique to detect nuclear factor-κB (NF- κB) mRNA. Results: Only nine out of 34 women with spontaneous abortion were positive for HCMV early protein, with a significantly higher expression of NF-κB in HCMV positive cases as compared with HCMV negative and the control group (p = 0.001). Conclusion: This study strengthen the possibility that HCMV infection may play an important role in the pathology of pregnancy loss on multidirectional bases include inducing the expression of the transcriptional factor; NF-κB.